Sistem Pengembangan Chatbot Whatsapp Untuk Monitoring Hasil Pembelajaran Siswa Sekolah Menngah Kejuruan - Zihan Abidin; Muhtajuddin Danny; Asep Muhidin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Service is an activity or sequence that occurs in direct interaction between a person and another person or machine physically, and provides customer satisfaction. In serving or accessing information at SMK Negeri 3 Kuningan, they still use conventional methods, so it takes time to access them. As students have to do when they are going to ask about grades with certain subjects, they have to meet the teacher in question. The value recap carried out by the teacher also still uses manuals with the use of file books. Therefore, with this problem, a chatbot is made as a solution to this problem as a forum to solve problems in finding this information. In addition, the value recapitulation also uses a website system to facilitate data processing. The development of this chatbot uses the waterfall method. By developing a system in the form of a chatbot as a student tool and a website as a teacher tool, it is hoped that it will be able to speed up the process of monitoring grades. The results of the study were able to produce a whatsapp chatbot application that students could use to monitor grades and a website that teachers could use to recapitulate grades.